Refractive outcomes of small lenticule extraction (SMILE) Pro® with a 2 MHz femtosecond laser - Saad, Amr; Klabe, Karsten; Kirca, Mücella; Kretz, Florian A. T.; Auffarth, Gerd U.; Breyer, Detlev R. H. (International ophthalmology, 2024)
PURPOSE: To evaluate the initial visual outcomes of Small Incision Lenticule Extraction (SMILE) Pro® using a 2 MHz femtosecond laser (VisuMax 800, Carl Zeiss Meditec) and to assess the efficacy, safety, predictability, accuracy, and complication rate. - METHODS: This retrospective analysis included eyes which underwent the SMILE Pro® procedure using VisuMax 800 femtosecond laser to correct myopia. All surgeries were performed by one surgeon (DB). Follow-up was conducted 3 months postoperatively to evaluate visual outcomes after neuroadaptation, corrected visual acuity (CDVA) and intra- and postoperative complications. - RESULTS: One hundred and fifty-two eyes of 82 patients (mean age 31 ± 6 years) results at 3 months are presented. The mean spherical equivalent (SE) was - 4.44 ± 1.86 D preoperatively while -0.24 ± 0.32 D postoperatively. 99% of eyes achieved SE within ± 1.0 D of attempted correction and 91% were within ± 0.5 D. Efficacy index was 0.93 while the safety index was 1. No complications occurred intra- or postoperatively. No eyes lost more than 1 line of their preoperative CDVA. All highly myopic eyes (- 6.25 to - 10.00 D; n = 18) achieved 20/20 at 3 months postoperatively and were within 0.5 D from the attempted SE and no eyes lost more than 1 line of CDVA. - CONCLUSION: The SMILE Pro® is a safe, efficient, and predictable procedure for the treatment of myopia and myopic astigmatism, with comparable results of conventional SMILE surgery. High myopic eyes achieve better results than low and moderate myopia. No complications were recorded in our patients.